Germination of Moringa Oleifera L. with the application of ecomic ® and two synthetic biostimulants under controlled conditions - Bécquer, C. J.; Puentes, Adelaida B. (Cuban Journal of Agricultural Science, 2024)
Under controlled conditions, the effect of EcoMic® (Glomus cubense), TOMATICID and VIUSID® AGRO on the germination of Moringa oleifera Lam. was evaluated. The experiment was carried out in polyurethane foam trays, in a glass house. Four seeds were sown in each little well, which contained 120 g of substrate. Seeds were inoculated with the bioproducts, according to the recommendations of the manufacturer. A completely randomized design was applied, with 10 treatments and 10 repetitions. An ANOVA analysis was performed and differences among means were determined according to LSD of Fisher. In accumulated germination, 10 days after sowing, treatment 10 (EcoMic®, at the time of sowing, and VIUSID® AGRO, five days after sowing, 43.81%) was superior to the absolute control and the treatments 3 (EcoMic®), 4 (TOMATICID), 5 (VIUSID® AGRO) and 7 (EcoMic® VIUSID® AGRO) at the time of sowing. In partial germination, treatment 10 (30.71%) five days after sowing, as well as treatments 8 (EcoMic® + VIUSID® AGRO + TOMATICID, 45.52%) and 6 (EcoMic® + TOMATICID, 41.53%) at the time of sowing, were superior to the rest, except for 9 (EcoMic®, ST + TOMATICID) five days after sowing. In the total germination index, treatment 10 (14.46) surpassed the others, except for treatment 8 and the fertilized control. Germination speed index showed that treatment 10 (0.45) was superior to the others. It is concluded that the combination of EcoMic® and VIUSID® AGRO, five days after sowing, as well as that of EcoMic® + VIUSID® AGRO + TOMATICID and EcoMic® + TOMATICID, at the time of sowing, accelerated partial germination at 10 days after sowing with respect to the rest of treatments. The combination of EcoMic® and VIUSID® AGRO five days after sowing had a significant influence on the speed of germination and uniformity of seed vigor, which could constitute an advantage for the establishment of plantlets in the nursery. The effect of the bioproducts on germination capacity of seeds corresponded to the effect on their vigor and uniformity.